2014
DOI: 10.4161/biom.28764
|View full text |Cite
|
Sign up to set email alerts
|

Poly(vinyl alcohol) hydrogel coatings with tunable surface exposure of hydroxyapatite

Abstract: Insufficient bone anchoring is a major limitation of artificial substitutes for connective osteoarticular tissues. The use of coatings containing osseoconductive ceramic particles is one of the actively explored strategies to improve osseointegration and strengthen the bone-implant interface for general tissue engineering. Our hypothesis is that hydroxyapatite (HA) particles can be coated robustly on specific assemblies of PVA hydrogel fibers for the potential anchoring of ligament replacements. A simple dip-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…As shown in Fig. 8, the surface coating on bundle of PVA hydrogel fibres can be tuned from 0 to over 55% by increasing amount of HAp in PVA/HAp weight ratio (from 0.4 to 0.1).Further, it was observed that these coatings adhere well to the fibre bundles and detach by crack propagation inside the coating and may provide a guidance to select coatedimplants for anchoring artificial ligaments[249]. Chen et al 2015 prepared PVA-HAp hydrogel for articular cartilage (as a porous hydrated tissue covering the end of each bone at the joints[250]) and investigated the fluid load support mechanism under conditions of swing friction followed by the influence of load and swing angle on fluid load support.The swinging of Co-Cr-Mo ball on the surface of composite hydrogel showed the support mechanism, where its fluid flows to the surface, thereby reducing the friction between the ball and composite hydrogel and a small amount of fluid flows back inside the composite hydrogel, thereby restoring its mechanical properties.…”
mentioning
confidence: 77%
“…As shown in Fig. 8, the surface coating on bundle of PVA hydrogel fibres can be tuned from 0 to over 55% by increasing amount of HAp in PVA/HAp weight ratio (from 0.4 to 0.1).Further, it was observed that these coatings adhere well to the fibre bundles and detach by crack propagation inside the coating and may provide a guidance to select coatedimplants for anchoring artificial ligaments[249]. Chen et al 2015 prepared PVA-HAp hydrogel for articular cartilage (as a porous hydrated tissue covering the end of each bone at the joints[250]) and investigated the fluid load support mechanism under conditions of swing friction followed by the influence of load and swing angle on fluid load support.The swinging of Co-Cr-Mo ball on the surface of composite hydrogel showed the support mechanism, where its fluid flows to the surface, thereby reducing the friction between the ball and composite hydrogel and a small amount of fluid flows back inside the composite hydrogel, thereby restoring its mechanical properties.…”
mentioning
confidence: 77%
“…nHA is the bioactive and osteoconductive chemical component in bone and the calcified zone in cartilage. 54-56 Hydroxyapatite and its derivatives have been studied and shown to increase cell-scaffold performance via incorporation within a bulk matrix as well as surface adsorption 57-59 and nucleation. 60-62 Through a hydrothermal treatment method, our lab can synthesize more biomimetic nHA with excellent control of the crystalline phase and surface morphology at the nano scale.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, one of the key nanomaterials utilized in the manufacture of our graded osteochondral scaffold, nHA, can provide several key benefits to include: mechanical reinforcement, nanotexturization, and osteoconductivity. As a bioactive and osteoconductive chemical component in bone and the calcified zone in cartilage, 25,38,39 hydroxyapatite and its chemical derivatives have been extensively studied and shown to increase cell-scaffold performance via incorporation within a bulk matrix 3 as well as surface adsorption [40][41][42] and in situ nucleation. [43][44][45] Through a hydrothermal treatment method, our lab readily synthesizes biomimetic nHA with excellent control of nano scale crystallinity and surface morphology.…”
Section: Table-top Sl Printing For the Fabrication Of Bioactive Grade...mentioning
confidence: 99%